The fisher king [videorecording (DVD)] - Williams, Robin, 1951-2014; Bridges, Jeff, 1949-; Plummer, Amanda; Ruehl, Mercedes (Criterion collection ;, 2015)
Parry is a homeless history professor who lives in a fantasy world full of castles, Red Knights, and damsels in distress. Jack is New York's number one shock deejay, until the day his off-hand arrogance triggers a tragedy that ruins his career. Penniless and without prospects, Jack finds himself plucked from disaster by the most improbable of saviors, Parry.